Suffering and prejudice: Do negative emotions predict immigration concerns? - Sumit S. Deole; Yue Huang (Global Labor Organization (GLO), 2020)
Despite being a regular suspect, a causal role of residents' emotions in predicting their opposition to international immigration has not been investigated. Using the individual-level panel data from Germany, we study the impact of the individual's experience of negative emotions (sadness, fear, and anger) on immigration concerns and bridge this gap in the literature. After controlling for person fixed effects and a battery of individual-level and macroeconomic controls, we find that negative emotions are statistically and significantly associated with the respondent's immigration concerns. The association holds for male as well as female respondents. To estimate the causal effects of negative emotions, we exploit the exogenous variation in negative emotions induced by the death of a parent or the change in averages of daily temperature and employ IV fixed effects regressions. Our findings suggest that, while within-person changes in the respondent's feelings of anger affect immigration concerns among all respondents, the feelings of sadness and fear affect immigration concerns only among females. The impact of sadness and fear is more forceful among females who are not always-working during the sample period, older in age, and rarely use online social media.
Keywords: D91; F22; J18; 330; Emotions; negative emotions; immigration concerns; public policy